PUNISHMENT AND OTHER PENAL MEASURES - Maizer Chankseliani (European Scientific Journal, ESJ, 2012)
For centuries, the only purpose of punishment was to punish an offender and it should be equal to the damagecauses by the crime. While the development of the humankind, these purposes changed and became more human andtolerant. That is why the aims of punishment changed and criminal law should consider the other penal measures,besides punishment.In the current Criminal Law, the purposes of punishment are: to punish an individual without causing physical pain orhumiliating him/her; to reform a criminal, re-socialization and rehabilitation of the convicted person; to prevent thecrime by the same offender or other members of society.The conception and purposes of punishment are various in the Penal Codes of different countries, but the mainprinciples are the same.The list of penalties are also different in the Criminal Laws of different legal systems. Some Penal Codes containthe exact list of penalties, also the list of other penal measures which are called “security measures”.There is no definition of security measures in the current Criminal Law. In general, these are the compulsory measures ofmedical and correctional nature.The principles of sentencing are also various, but the major are: dangerousness of a criminal act; guilt of an offender,his/her personality and past. That is why the most Penal Codes contain penalties and security measures that may beimposed in special cases.Most of the countries also differentiate adult and juvenile offenders. While common penalties may be imposed on anadult offender, special penalties may be imposed on a minor.